2022
DOI: 10.1017/ice.2022.50
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two coronavirus disease 2019 (COVID-19) vaccines (viral vector and inactivated viral vaccine) against severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection in a cohort of healthcare workers

Abstract: Objectives: We aimed to investigate real-world vaccine effectiveness (VE) for Oxford-AstraZeneca (ChAdOx1) and CoronaVac against laboratory-confirmed COVID-19 infection among healthcare workers (HCWs). Methods: We conducted a retrospective cohort study among HCWs (aged ≥18 years) working in a private healthcare system in Brazil between January 1, 2021 and August 3, 2021. To assess VE, we calculated VE=1-RR (rate ratio), with RR determined by adjusting Poisson models with the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In the meta-analysis fixed-effects model was used when I 2 <50%, and the random-effects model was used when the I 2 > 50% to pool the VE data with 95% confidence intervals (CIs). Among the included articles, RCT evidence from Turkey ( 16 ), Brazil ( 18 , 36 ), Indonesia ( 17 ), and the United Arab Emirates and Bahrain ( 8 ); RWE data from Chile ( 9 , 30 , 34 ), Brazil ( 19 , 24 , 27 , 35 ), Argentina ( 22 ), Thailand ( 21 ), Serbia ( 23 ), United Arab Emirates ( 25 , 31 ), Iran ( 26 ), China ( 20 , 28 , 29 ), Colombia ( 33 ), Hungary, and Turkey ( 32 ) were included. As the heterogeneity among RCT and RWE was huge, and I 2 was consistently higher than 90%, this study was not able to pool efficacy and effectiveness data together; therefore, we have done subgroup analysis for RCT and RWE studies of adult, and for the elderly and children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta-analysis fixed-effects model was used when I 2 <50%, and the random-effects model was used when the I 2 > 50% to pool the VE data with 95% confidence intervals (CIs). Among the included articles, RCT evidence from Turkey ( 16 ), Brazil ( 18 , 36 ), Indonesia ( 17 ), and the United Arab Emirates and Bahrain ( 8 ); RWE data from Chile ( 9 , 30 , 34 ), Brazil ( 19 , 24 , 27 , 35 ), Argentina ( 22 ), Thailand ( 21 ), Serbia ( 23 ), United Arab Emirates ( 25 , 31 ), Iran ( 26 ), China ( 20 , 28 , 29 ), Colombia ( 33 ), Hungary, and Turkey ( 32 ) were included. As the heterogeneity among RCT and RWE was huge, and I 2 was consistently higher than 90%, this study was not able to pool efficacy and effectiveness data together; therefore, we have done subgroup analysis for RCT and RWE studies of adult, and for the elderly and children.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, with four records identified through other sources included, the metaanalysis comprised 24 eligible studies finally, including four phase 3 studies (8, 16-18) and 20 real-world studies (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (including 2 RWE shared by company). The studies mentioned virus strains were as follows: four of Alpha (22,23,31,32), one of Beta (31), three of Gamma (19,22,27), five of Delta (20,21,25,28,29), one of Omicron (30), while the others did not mention the virus type. The majority of the included studies focused on adults, one focused on children aged 3-5 years (30), and three focused on the elderly aged over 60 years (22,23,33,35).…”
Section: Meta Analysis Of Vaccine Effectivenessmentioning
confidence: 99%
“…A multi-centric study with a sample size of 1446 patients conducted in four tertiary care hospitals in Kerala, South India, showed that severity of infection, duration of hospital stays, need for ventilation, and death were significantly less among vaccinated patients vs. unvaccinated patients [ 78 ]. Similarly, another retrospective cohort study conducted in Brazil reported the reduction in hospital stays and the need for mechanical ventilation in infected health care workers vaccinated with Oxford-AstraZeneca (ChAdOx1) or Corona vac [ 79 ]. Similar studies conducted elsewhere have shown the efficacy of vaccines in reducing the severity of COVID-19 and the length of hospital stay [ 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative test case–control study from Canada showed that AZD1222 against documented infection for Gamma was surprisingly effective ( 50 ). However, the study from Brazil revealed that the VE of double-dose AstraZeneca-Vaxzevria vaccine was 88.1% (95% CI: 82.8–91.7) ( 56 ) ( Table 3 ).…”
Section: Covid-19 Vaccine Effectiveness Against Variantsmentioning
confidence: 99%